Rancangan Penilaian Kinerja Karyawan dengan Metode Behaviorally Anchor Rating Scale (BARS) - Astari, Karima (LPPM Universitas Informatika dan Bisnis Indonesia, 2023)
Employee performance appraisal is very important in the workplace. This relates to the decisions that will be made by the company about the productivity of its employees. Faculty X at University Y also conducts employee performance appraisals like other companies do. Grade scales and employee daily work reports are the methods used by faculty X at University Y. These methods still need to be considered effective in actual practice. This is because many employees still consider formality, subjective assessment, the need for clear and measurable standards, and feedback on employee performance. To overcome this, the researchers developed a performance appraisal method, the Behavioral Anchor Rating Scale (BARS) method. The BARS method combines the benefits of narrative methods, critical incidents, and measurable scales (a graphical rating type) by creating standardized rating scales with specific behavioral examples of good or bad employee performance. This solves the problem of evaluating employee performance which tends to be subjective. The performance appraisal problem for employees at Faculty X can be solved using the BARS method. This study uses a qualitative approach with a five-step model data collection technique to make a BARS performance assessment followed by group discussions/participation from competent internal companies combined with qualitative interviews and uses thematic analysis for data analysis.